Radiological mapping of Kelantan, Malaysia, using terrestrial radiation dose rate - Garba, N. N. (Taylor and Francis Ltd., 2016)
Measurements of the environmental terrestrial gamma radiation dose rate (TGRD) in each district of Kelantan state, Malaysia, were carried out using a portable hand-held radiation survey meter and global positioning system. The measurements were done based on geology and soil types of the area. The mean TGRD was found to be 209 nGy h–1. Few areas of relatively enhanced activity were observed in Pasir Mas, Tanah Merah and Jeli districts, which have a mean TGRD between 300 and 500 nGy h–1. An isodose map of the area was produced using ArcGIS software version 9.3.